2008
DOI: 10.1111/j.0908-8857.2008.04047.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change affects breeding of reed warblers Acrocephalus scirpaceus

Abstract: Between 1970 and 2006 reed warblers Acrocephalus scirpaceus started breeding progressively earlier; both the initiation of breeding (the earliest first egg dates) and peak of breeding (median first egg dates) advanced. Median first egg dates correlated significantly with increasing MayÁJuly mean temperatures. However, in contrast to other studies showing the advancement in laying dates, the end of the season did not shift. As a result, the breeding season is now longer increasing re-nesting opportunities. Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 29 publications
7
101
0
2
Order By: Relevance
“…Given that there is a strong within-season decline in clutch size among bird species (Crick et al 1993), our data suggest that the Fieldfares' increase in mean brood size is caused by shifting its entire breeding season toward earlier dates, while in Song Thrushes the decline is driven by extending its breeding season with many late small-clutched broods. A long-term increase in brood size has been found in other open-nesting species, for example, Red-backed Shrikes Lanius collurio (Hušek & Adamík 2008), Eurasian Reed Warblers Acrocephalus scirpaceus and Great Reed Warblers Acrocephalus arundinaceus (Schaefer et al 2006, but see Halupka et al 2008).…”
Section: Trends In Breeding and Climatementioning
confidence: 94%
“…Given that there is a strong within-season decline in clutch size among bird species (Crick et al 1993), our data suggest that the Fieldfares' increase in mean brood size is caused by shifting its entire breeding season toward earlier dates, while in Song Thrushes the decline is driven by extending its breeding season with many late small-clutched broods. A long-term increase in brood size has been found in other open-nesting species, for example, Red-backed Shrikes Lanius collurio (Hušek & Adamík 2008), Eurasian Reed Warblers Acrocephalus scirpaceus and Great Reed Warblers Acrocephalus arundinaceus (Schaefer et al 2006, but see Halupka et al 2008).…”
Section: Trends In Breeding and Climatementioning
confidence: 94%
“…On the other hand, a higher productivity of offspring related to climate-driven favourable conditions on the breeding grounds may counterbalance this effect. For example, studies of two populations of Reed Warblers from central Europe (Schaefer et al 2006;Halupka et al 2008) revealed that increased temperatures observed in recent years during the breeding season were correlated with a higher number of nestlings produced by breeding pairs. However, as various recent estimations of population trends for the Reed Warbler have produced equivocal results (Ockendon et al 2012(Ockendon et al , 2014Vickery et al 2014, Inger et al 2015, further detailed studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades large-scale climatic changes have significantly affected local weather conditions in many parts of the globe (Houghton 2015). As such, changes in weather parameters may occur at the wintering or breeding grounds, as well as at stopover sites (Halupka et al 2008;Zwarts et al 2009;García-Mozo et al 2011). Large-scale climatic changes may also cause weather anomalies along the migratory routes (Tøttrup et al 2012) that may affect the survival or population dynamics of various bird species (Sanderson et al 2006;Ockendon et al 2014;Inger et al 2015;Jansen et al 2015;Woodworth et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall patterns and temperature fluctuations determine, for example, reed growth (Garris et al 2015) and food availability (Gwitira et al 2015) and thereby affect distribution, density, spring arrival dates and breeding success of reed bird communities (e.g. Virkkala et al 2005;Halupka et al 2008;Eglington et al 2015).…”
Section: Song Variation and Climatementioning
confidence: 99%